Awareness and knowledge of radiation protection in interventional laboratory: a comparative study between Australian and Saudi Arabian hospitals - Alahmari, Mohammed Ali S. (Curtin University, 2015)
This research project aims to investigate the attitudes and practices of medical staff engaged in interventional procedures regarding personal radiation protection, as well as the relationship between their uses of protective devices and training in radiation protection. Research findings of this study show the necessity and efficacy of radiation protection training for providing a safer environment when utilising the fluoroscopic image-guided machines in clinical practice.